RETROFITTING SUBURBAN HOMES FOR RESILIENCY: A PROTOTYPE DECISION SUPPORT SYSTEM - Prevost, Glen (My University, 2012)
North American suburbs are facing decline and obsolescence. They cannot meet the needs of North America’s ageing society, future climate change, or higher energy prices. Compounded with their negative environmental impact, non-resilient is an appropriate label for North American suburbs.
Resilient suburban communities can be realized through retrofitting to meet current and future needs. Community scale retrofitting is in the early stages of development. House-level retrofitting tools exist but must be synthesized into a useable form for homeowners.
Homeowners arguably have the largest stake in the future of the suburbs for both financial and social reasons. Empowering them with tools to make their suburban home and community more resilient is considered to be desirable.
This thesis empowers homeowners by developing a prototype decision support system (DSS) that will help them (or their contractors) make choices about adapting and retrofitting their home for resilience. This Microsoft Excel-based DSS addresses the following suburban needs: new housing types, reducing the environmental impacts of the home, and decreasing reliance on fossil fuels. The DSS does this through three constituent ‘modules’.
The first module, Dividing Suburban Homes, demonstrates the feasibility of dividing large suburban homes into multifamily dwellings. The second module, Sustainable Additions, selects resilient building materials for housing additions. The last module, Reducing the Home’s Environmental Impact, helps homeowners choose methods for reducing the environmental impact and fossil fuel usage of their home.
Through these three modules, this DSS addresses a considerable number of the current and anticipated issues facing the suburbs.
Keywords: suburbs; suburban; home design; decision support system; energy analysis; Architectural Engineering; Computer-Aided Engineering and Design; Environmental Engineering; Urban, Community and Regional Planning; Architectural Engineering